Network meta-analysis of integrated traditional Chinese and Western medicine in the treatment of Sjogren’s syndrome - Ma, Xieli; Liu, Zixia; Chang, Tian; Yao, Chuanhui; Yang, Yuchen; Shang, Biyue; Liu, Jiameng; Xia, Congmin; Gong, Xun; Jiang, Quan (Frontiers in Pharmacology, 2024)
Abstract Objective: To evaluate efficacy and safety of traditional Chinese medicine(TCM) combined with Western medicine in treatment of Sjogren's syndrome (SS). Methods: CNKI, WanFang, VIP, CBM, Sinomed, PubMed, Embase, and Web of Science were searched to collect randomized controlled trials (RCTs) of TCM combined with conventional western medicine(CWM) in treating SS from the time of their estalishment to May 2023. The researchers independently screened the literature and extracted data for quality evaluation. Analyses were performed using Review Manager(version 5.4) and R-4.3.1. Results: A total of 66 RCTs were included, with a sample size of 5052, involving four kinds of TCM (total glucosides of paeony capsules,tripterygium glycosides tablet,Xinfeng capsule and Xinfeng capsule)and three kinds of CWM(hydroxychloroquine sulfate,Iguratimod and glucocorticoid). The network meta-analysis results showed that IGU+HCQ+TGP ranked the highest in reducing ESR and IgG and improving the Schirmer test when the three drugs were combined. When the two drugs are combined, IGU+GC and TGT+TGP are good choices for reducing erythrocyte sedimentation rate(ESR) and Immunoglobulin G(IgG). Although TGP+HCQ vs HCQ had the most studies, TGP combined with HCQ did not rank high in each outcome indicator. It is recommended to use TGT and XFG in decreasing ESR and IgG for a single drug. JJQR have an advantageous role in relieving xerostomia and dry eyes. Conclusion: TCM combined with CWM has a very significant effect on treating SS compared with CWM alone.According to the network meta-analysis, the best intervention measures of different TCMs for different outcome indicators were obtained.